PC tools deluxe : an essential guide - Ashley, Ruth.; Fernandez, Judi N. (New York : Wiley, 1990)
This book shows how to use PC tools to your best advantage. It goes beyond the documentation that comes with the package to show you what to do and what not to do as well as how to recover from problem situations.
"Covers version 6.0"--Cover. includes illustrations
Includes index.
ijb 16/01/2019
Loans
Keywords: Utilities (Computer programs)